Controlled in vivo Bone Formation and Vascularization Using Ultrasound-Triggered Release of Recombinant Vascular Endothelial Growth Factor From Poly(D,L-lactic-co-glycolicacid) Microbubbles - Gong, Yong; Li, Songjian; Zeng, Wei; Yu, Jianing; Chen, Yan; Yu, Bo (Frontiers in Pharmacology, 2019)
Bone defects are challenging to treat in musculoskeletal system due to lack of vascularization. Biomaterials with internal vascularization ability and osteoinduction bioactivity are promising strategies for orthopedic applications. Vascular endothelial growth factor (VEGF) has been widely used for angiogenesis and osteogenesis. Here, we developed VEGF loaded PLGA microbubbles (MBs) for improvement of angiogenesis and osteogenesis in bone defect repair in combination with ultrasound-targeted microbubble destruction (UTMD). Release profile showed UTMD promoted the burst release of VEGF from PLGA MBs. We subsequently investigated the combination of ultrasound application with VEGF MBs for in vitro osteogenesis. The results demonstrated that the expression of osteogenesis-related genes and calcium deposits were increased by VEGF MBs in combination of UTMD. Micro-computed tomography (micro-CT) and histological analysis were conducted 4 and 8 weeks post-surgery. In vivo results show that VEGF MBs in combination of UTMD could significant enhance new bone formation and vascular ingrowth at the defect site in a rat calvarial defect model. In summary, VEGF MBs in combination of UTMD could augment bone regeneration and vascularization at calvarial bone defects and holds huge potential for clinical translation.